The Great Migration of Serbs and the Question of the Serbian Ethnic and Religious Community in the Habsburg Monarchy - Točanac Radović, Isidora (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
During the Great Turkish War (1683–1699), tens of thousands of Serbs, with their patriarch and clergy, fled from the Ottoman territory and arrived in the territories under the Habsburg rule. During this event, known as the Great Migration of 1690, the majority of the refugees settled in the areas that had been part of the Kingdom of Hungary before the Ottoman conquest and then conquered by the Habsburg army in the Great Turkish War. The newly settled population had the potential to revitalise the territory it inhabited, both economically and demographically. Accepting them into his country and under his rule, Emperor Leopold I granted Serbs the right to profess the Orthodox faith freely and the right to have their own church organisation by his special edicts issued between 1690 and 1695. The ruler regulated the rights, income and status of the Orthodox clergy, granted the Serbian people the right to participate in the election of their church leader, released them from paying tithes to the Roman Catholic Church, etc. The Privileges of Leopold I that granted rights to Serbs as the faithful of the Orthodox Church determined the legal and political status of the Serbian people in the Kingdom of Hungary as part of the Habsburg Monarchy. In this way, the Serbian Orthodox population was singled out from the established legal framework and became a special category both in the legislation and in the class society of the Kingdom of Hungary. The aim of this paper is to answer the question of how an Orthodox community became privileged in a state where the Roman Catholic faith was dominant. The motives of the rulers are explained, the view of the Hungarian nobility, the county authorities and the Roman Catholic Church on the Privileges is presented, as well as the ways in which Serbs tried to defend their privileged rights.